Novel silica stabilization method for the analysis of fine nanocrystals using coherent X‐ray diffraction imaging. (23rd June 2016) - Monteforte, Marianne; Estandarte, Ana K.; Chen, Bo; Harder, Ross; Huang, Michael H.; Robinson, Ian K.
Abstract : The feasibility of a novel one‐step `drop‐cast' stabilization method as a prompt and efficient approach to extend the accessible size regime of the Bragg coherent diffraction imaging (BCDI) technique is demonstrated. Fine chemically synthesized nanocrystals with dimensions sub‐100 nm were stabilized and from BCDI measurements three‐dimensional reconstructions of the nanocrystals were achieved. Abstract : High‐energy X‐ray Bragg coherent diffraction imaging (BCDI) is a well established synchrotron‐based technique used to quantitatively reconstruct the three‐dimensional morphology and strain distribution in nanocrystals. The BCDI technique has become a powerful analytical tool for quantitative investigations of nanocrystals, nanotubes, nanorods and more recently biological systems. BCDI has however typically failed for fine nanocrystals in sub‐100 nm size regimes – a size routinely achievable by chemical synthesis – despite the spatial resolution of the BCDI technique being 20–30 nm. The limitations of this technique arise from the movement of nanocrystals under illumination by the highly coherent beam, which prevents full diffraction data sets from being acquired. A solution is provided here to overcome this problem and extend the size limit of the BCDI technique, through the design of a novel stabilization method by embedding the fine nanocrystals into a silica matrix. Chemically synthesized FePt nanocrystals of maximum dimension 20 nm and AuPd nanocrystals in the size range 60–65 nm were investigated with BCDI measurement at beamline 34‐ID‐C of the APS, Argonne National Laboratory. Novel experimental methodologies to elucidate the presence of strain in fine nanocrystals are a necessary pre‐requisite in order to better understand strain profiles in engineered nanocrystals for novel device development.